2017
DOI: 10.2174/1874210601711010367
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sinonasal Anatomic Variations in the Development of Maxillary Sinusitis: A Cone Beam CT Analysis

Abstract: Background:Several anatomical variations can lead to the inflammation of the paranasal sinuses; therefore, surgeons should be familiar with these variations and their impacts on the status of the paranasal sinuses.Objectives:The present study aimed to determine the prevalence of Haller cells and its association with patients’ sex and age. Furthermore, the relationships between the presence and size of Haller cells, deviation of the uncinate process and size of the maxillary sinus ostium with the occurrence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 21 publications
3
18
0
Order By: Relevance
“…The form of RS (CRS vs ARS) was not delineated, but the study suggests that obstruction of the OMC can lead to ethmoid and maxillary mucosal disease. Similarly, Khojastepour et al 333 found that infraorbital cells are associated with maxillary mucosal disease on cone beam CT scan in patients presenting for rhinoplasty evaluation. In addition, other studies have demonstrated that sphenoethmoidal cells (Onodi cells) may be associated with radiographic sphenoid mucosal thickening, again, ostensibly from narrowing of the natural sinus ostia 787 …”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 93%
See 1 more Smart Citation
“…The form of RS (CRS vs ARS) was not delineated, but the study suggests that obstruction of the OMC can lead to ethmoid and maxillary mucosal disease. Similarly, Khojastepour et al 333 found that infraorbital cells are associated with maxillary mucosal disease on cone beam CT scan in patients presenting for rhinoplasty evaluation. In addition, other studies have demonstrated that sphenoethmoidal cells (Onodi cells) may be associated with radiographic sphenoid mucosal thickening, again, ostensibly from narrowing of the natural sinus ostia 787 …”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 93%
“…There is mixed evidence supporting the association of ARS (definition based on clinical suspicion and mucosal thickening on imaging) and anatomical variants specific to concha bullosa, 305,329–331 nasal septal deviation, 305,329,331,332 infraorbital ethmoid cell, 305,329–331,333 infundibulum stenosis, 305,329,330,333 or agger nasi cell 329,331 . There is also limited evidence of association with radiographic mucosal thickening and findings of intralamellar cells, 329 MT hypertrophy, 329 aerated uncinate process, 329,330 and asymmetry of the ethmoid roof 330 .…”
Section: Acute Rhinosinusitis (Ars)mentioning
confidence: 99%
“…The paradoxical middle turbinate is thought to cause recurrent rhinosinusitis and prevent access to the ostiomeatal unit during surgery [2]. Paradoxical middle turbinate can cause recurrent infundibular disease and sometimes headache [13,20]. In our study, the paradoxical middle turbinate occurred on the right side 12.1% of the time, on the left side 8.3% of the time and on both sides 5.7% of the time.…”
Section: Discussionsupporting
confidence: 44%
“…In several studies, the prevalence of Agger nasi cells varied between 61.4% and 98.5%. However, in 90.6% of cases, the presence of agger nasi cells was bilateral [4,13]. Unlike other studies, agger nasi cells were found on the right side in 51% patients, on the left side in 51% of patients and on both sides in 47.1% of patients.In addition, patients with agger nasi cell had a higher incidence of Haller cells and maxillary septa.…”
Section: Discussionmentioning
confidence: 72%
“…7 Currently, cone-beam computed tomography (CBCT) is the technique of choice for various 3D imaging purposes in dentistry. 8 However, in cases in which high-density, metallic objects, such as titanium implants, are positioned within the field of view (FOV), image quality is degraded as a result of streaking and beam-hardening artifacts, rendering the bone around the implant difficult to evaluate. 9 The severity of these artifacts, which in some cases can be sufficient to mask peri-implant bone defects, depends on several factors, including the type of CBCT device used, the FOV dimensions, the position of the object within the FOV, and the application of metal artifact reduction algorithms.…”
Section: Introductionmentioning
confidence: 99%